Optimal decoding and information transmission in Hodgkin-Huxley neurons under metabolic cost constraints - Kostal, Lubomir; Kobayashi, Ryota (Bio Systems, 2015)
Information theory quantifies the ultimate limits on reliable information transfer by means of the channel capacity. However, the channel capacity is known to be an asymptotic quantity, assuming unlimited metabolic cost and computational power. We investigate a single-compartment Hodgkin-Huxley type neuronal model under the spike-rate coding scheme and address how the metabolic cost and the decoding complexity affects the optimal information transmission. We find that the sub-threshold stimulation regime, although attaining the smallest capacity, allows for the most efficient balance between the information transmission and the metabolic cost. Furthermore, we determine post-synaptic firing rate histograms that are optimal from the information-theoretic point of view, which enables the comparison of our results with experimental data.
Keywords: Ion Channel Gating; adenosintrifosfát; Models, Neurological; Optimal decoding; Humans; gating iontového kanálu; iontové kanály; modely neurologické; Computer Simulation; akční potenciály; Neuronal coding; Information Storage and Retrieval; lidé; zvířata; Action Potentials; neurony; Information transfer; Synaptic Transmission; Energy Metabolism; Adenosine Triphosphate; počítačová simulace; energetický metabolismus; nervový přenos; Neurons; Ion Channels; Animals; Membrane Potentials; membránové potenciály; ukládání a vyhledávání informací